(untitled) (Czech Journal of International Relations, 1998)
Seymour M. Lipset: American Exceptionalism: A Double-Edged Sword (Dvojsečná výjimečnost Ameriky). W. W. Norton & Co., New York 1996,352 stran, ISBN 0-393-03725-8.